2004
DOI: 10.1073/pnas.0305096101
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and inducible trypsin proteinase inhibitor production incurs large fitness costs in Nicotiana attenuata

Abstract: Plant trypsin proteinase inhibitors (TPIs) are potent herbivore-and jasmonate (JA)-induced defenses, but support for the commonly invoked explanation for their inducible expression, namely their associated fitness costs, has been elusive. To determine whether the expression of TPIs incurs fitness costs, we expressed 175 bp of the seven-domain pi from Nicotiana attenuata in an antisense orientation in a TPI-producing genotype (WT) of N. attenuata to reduce TPI expression. Moreover, we expressed the full-length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
198
3
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(211 citation statements)
references
References 49 publications
8
198
3
2
Order By: Relevance
“…TrypPIs are likely to make large demands on a plant's N budget, but quantitative measures have not been made. However, TrypPI expression is known to be responsible for decreased growth and seed production in N. attenuata (Glawe et al, 2003;Zavala et al, 2004), which may reflect N-based tradeoffs between growth and TrypPI production. Surprisingly, the expression levels of TrypPI transcripts in OS-elicited LN plants were significantly higher than those in HN plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TrypPIs are likely to make large demands on a plant's N budget, but quantitative measures have not been made. However, TrypPI expression is known to be responsible for decreased growth and seed production in N. attenuata (Glawe et al, 2003;Zavala et al, 2004), which may reflect N-based tradeoffs between growth and TrypPI production. Surprisingly, the expression levels of TrypPI transcripts in OS-elicited LN plants were significantly higher than those in HN plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We elicited plants by treating mechanical wounds with M. sexta OS and measured the timing and magnitude of the JA and SA burst, which are reliable signatures of the plant's ''recognition'' that likely organize much of the tailoring of the defense responses. In addition to wounding, OS applications, and herbivore attack, JA and MeJA applications are also known to elicit the accumulation of some herbivore-induced defense metabolites in N. attenuata, such as nicotine (Winz and Baldwin, 2001), TrypPI (Van Dam et al, 2001;Glawe et al, 2003;Zavala et al, 2004), VOCs (Halitschke et al, 2000;Lou and Baldwin, 2003), caffeoylputrescine, chlorogenic acid, and diterpene glycosides (DTGs; Keinänen et al, 2001;Lou and Baldwin, 2003). We measured the elicited mixture of both systemic and local responses in two phyllotactically adjacent leaves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, they could reflect a greater availability of nitrogen for nicotine biosynthesis due to the lack of nitrogen-intensive TPI production in AZ. However, given that AZ produces constitutively higher amounts of nicotine, whereas ET and JA can only influence induced nicotine production, and that such high constitutive nicotine production was not seen in a line of the UT accession that was silenced for TPI (Zavala et al, 2004a), we assume that changes in certain trans-or ciselement(s) in the regulation of nicotine biosynthesis have enabled AZ to produce more nicotine than UT.…”
Section: Natural Variation Of Secondary Metabolitesmentioning
confidence: 99%
“…How the TPI null allele was fixed in AZ is unclear because this mutation could have considerably lowered the ability of AZ to survive under herbivory pressure. Using TPI-silenced transgenic plants, Zavala et al (2004a) demonstrated that TPI production is costly under normal conditions because plants having lower TPI levels grow faster and have higher fitness due to the re-allocation of nitrogen; however, under selection pressure from herbivory, TPI-containing plants realize greater fitness due to the effectiveness of this defense (Zavala et al, 2004a(Zavala et al, , 2004b. One hypothesis is that after the TPI mutation event in AZ, there was very low selection pressure from herbivores; therefore, this null TPI allele was quickly fixed because it provided plants with higher fitness.…”
Section: Ecological and Evolutionary Significancementioning
confidence: 99%